Pesan Moral Dalam Kehidupan Sosial Dari Film Keluarga Cemara 2019 ( Analisis Semiotika Roland Barthes) - Resi Aulia; indrawati; ahmad harun yahya (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research was motivated by the many benefits of moral messages contained in the fir family film. This study aims to determine the benefits of moral messages from fir family films in social life using Roland Barthes' semiotic analysis method. This encourages researchers to find out how moral messages and benefits are in the scope of social life. The result of this study is the togetherness between families who support each other, do not leave each other under any circumstances and still maintain family harmony and integrity. Simplicity is also an important point in living life, living with gratitude for the blessings given by the almighty. Third, friendship is the most important part of friendship, so we will create a safe and comfortable atmosphere. Last is never give up, with never give up we can achieve what we want and we can survive in any condition. The approach used in this study is qualitative research, using observational and documentation research methods. This study also examines the denotative meaning and connotative meaning, that is, with dialogue / sound shown in the film then associated with moral messages that are useful in social life. Keywords: Moral Message, Film, Semiotics, Roland Barthes